Modeling the energetics of 100-m running by using speed curves of world champions - Arsac, L. M.; Locatelli, E. (Journal of Applied Physiology, 2002)
The present study aims to assess energy demand and supply in 100-m sprint running. A mathematical model was used in which supply has two components, aerobic and anaerobic, and demand has three components, energy required to move forward (C), energy required to overcome air resistance (Caero), and energy required to change kinetic energy (Ckin). Supply and demand were equated by using assumed efficiency of converting metabolic to external work. The mathematical model uses instantaneous velocities registered by the 1997 International Association of Athletics Federations world champions at 100 m in men and women. Supply and demand components obtained in the male champion were (in J/kg) aerobic 30 (5%), anaerobic 607 (95%), C 400 (63%), Caero 83 (13%), Ckin 154 (24%). Comparatively, a model that uses the average velocity of the male and female 100-m champions overestimates Ckin by 37 and 44%, respectively, and underestimates Caero by 14%. We argued that such a model is not appropriate because Ckin and Caero are nonlinear functions of velocity. Neither height nor body mass seems to have any advantage in the energetics of sprint running.